Acute bilateral serous retinal detachments with spontaneous resolution in a 6-year-old boy - Van Camp, Sophie (GMS Ophthalmology Cases, 2020)
A healthy 6-year-old boy presented with acute bilateral vision loss, multiple serous retinal detachments between the vascular arcades and a thickened choroid. Spontaneous resolution occurred over several weeks.We hypothesize that the clinical constellation in our patient is suggestive of acute exudative polymorphous vitelliform maculopathy (AEPVM) or might be an atypical presentation of Vogt-Koyanagi-Harada (VKH) disease. We propose that it was caused by an autoimmune-mediated activation of inflammatory cells at the level of the choroid, induced by an unknown trigger.